DEVELOPING AN ADAPTIVE DIGITAL FINANCE CAPABILITY FRAMEWORK FOR THE ARTIFICIAL INTELLIGENCE ERA: A NARRATIVE LITERATURE REVIEW AND THEORETICAL SYNTHESIS - Berlianna Dewi Setiawan; Maria Yovita R.Pandin; Amiartuti Kusmaningtyas (Yayasan Nuraini Ibrahim Mandiri, 2026)
The rapid advancement of Artificial Intelligence (AI) has accelerated the transformation of digital finance, requiring organizations to develop adaptive capabilities that extend beyond technology adoption. However, existing studies provide fragmented theoretical explanations by examining dimensions in isolation. This study aims to develop an Adaptive Digital Finance Capability Framework through a Narrative Literature Review (NLR) and Theoretical Synthesis. *To systematically filter secondary data from peer-reviewed literature indexed in Scopus, Web of Science, IEEE Xplore, and ScienceDirect (2020–2025), a transparent literature selection process was implemented using modified PRISMA guidelines.* The selected papers were evaluated using thematic content analysis and coding techniques. The results reveal that adaptive digital finance capability is structurally formed by six strategic dimensions: AI Readiness, Digital Financial Literacy, Digital Trust, Digital Governance, Financial Resilience, and Dynamic Capability. By shifting the analytical lens from technology adoption toward higher-order adaptive organizational capability, this study provides an integrated conceptual framework. This framework offers practical guidance for organizations and policymakers navigating AI-driven financial disruption to achieve a sustainable competitive advantage.